Occupational exposure to carcinogens in Australian road transport workers - Si, Si; Carey, Renee; Reid, Alison; Peters, S.; Glass, D.; Driscoll, T.; Darcey, Ellie; Fritschi, Lin (2015)
Background Road transport workers (RTWs) are at high risk of exposure to several occupational carcinogens. However, there are gaps in knowledge regarding the extent and the circumstances of exposure. As a sub-study of the Australian Work Exposures Study, this study investigated the prevalence of occupational exposure in Australian RTWs. Methods A random sample of Australian working population was invited to a telephone interview regarding their current jobs. An automated expert-assessment procedure was applied to self-reported job-related tasks using a web-based application. 162 RTWs were included in this study. Results RTWs were exposed to diesel exhaust (97%), solar ultraviolet radiation (78%), environmental tobacco smoke (55%), benzene (29%), silica (15%), and asbestos (10%) at work. Besides driving on roads, vehicle maintenance-related tasks were the major source of carcinogen exposures among RTWs. Discussion Most RTWs are exposed to at least one carcinogen at work. We have identified tasks where the use of control measures could potentially reduce exposures. Am. J. Ind. Med. © 2015 Wiley Periodicals, Inc.